The Sustainability of Renewable Energy in Europe - Bigerna, Simona (Springer, 2015)
This perspective is an ongoing challenge not only to the basic paradigm of efficient market decentralization and infinite supply of inputs in the long run, but also to the imperfect market and externality models. There is now recognition that the very survival of our society is at stake if we do not solve the issue of sustainability of our economic development. Indeed, the acknowledgement that fossil fuel reserves are finite or that emissions are dangerous to our health is not enough. We need comprehensive policies, credible policies, which can spur the necessary investment for the future of the Earth...